2020
DOI: 10.1155/2020/8833885
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Roles of STAT3 and Its Phosphorylation in Glioma

Abstract: Glioma is defined as a common brain tumor which causes severe disability or death. As many genes are reported to relate with glioma’s occurrence and development, their prognostic and therapeutic value still remains uncertain. This study aimed at investigating the association between STAT3/p-STAT3 and glioma prognosis. Nine studies (12 trials) scored ≥5 on the Newcastle-Ottawa scale were meta-analysed from the Medline, Embase, and Web of Science databases. We found that STAT3/p-STAT3 overexpression in glioma pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, Tang et al revealed that HSPB1 was crucial in ferroptosis-mediated cancer therapy 34 . STAT3 was associated with poor prognosis in gliomas 35 . Bao et al demonstrated that Ibrutinib could inactivate STAT3, thus reducing radiation resistance in glioma cells.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, Tang et al revealed that HSPB1 was crucial in ferroptosis-mediated cancer therapy 34 . STAT3 was associated with poor prognosis in gliomas 35 . Bao et al demonstrated that Ibrutinib could inactivate STAT3, thus reducing radiation resistance in glioma cells.…”
Section: Discussionmentioning
confidence: 95%
“…regulates cell proliferation, differentiation and metastasis (31,32). Studies have shown that STaT3/p-STaT3 is highly expressed in a variety of tumors and its activation product, p-STaT3, is associated with tumor grade and patient prognosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-3 can activate MMP-1 and other family members and its overexpression is associated with the growth and metastasis of various cancers, including breast cancer ( 30 ). When stimulated by external signals, STAT3 migrates to the nucleus in the form of activated p-STAT3, which stimulates cell growth and angiogenesis, activates the transcription of target genes and regulates cell proliferation, differentiation and metastasis ( 31 , 32 ). Studies have shown that STAT3/p-STAT3 is highly expressed in a variety of tumors and its activation product, p-STAT3, is associated with tumor grade and patient prognosis ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction and transcriptional activator 3(STAT3), a member of the STAT family, is the most critical in the STATS signaling pathway family. When stimulated by external signals, STAT3 migrates to the nucleus in the form of activated phosphorylated STATA3 (p-STATA3), which stimulates cell growth and angiogenesis, activates the transcription of target genes, and regulates cell proliferation, differentiation, and metastasis [24,25] . Studies have shown that STAT3/p-STAT3 is highly expressed in a variety of tumors, and its activation product, p-STAT3, is associated with tumor grade and patient prognosis [26,27] .…”
Section: Discussionmentioning
confidence: 99%